2020
DOI: 10.3390/cancers12010237
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Rb1 Enhances Glycolytic Metabolism in Kras-Driven Lung Tumors In Vivo

Abstract: Dysregulated metabolism is a hallmark of cancer cells and is driven in part by specific genetic alterations in various oncogenes or tumor suppressors. The retinoblastoma protein (pRb) is a tumor suppressor that canonically regulates cell cycle progression; however, recent studies have highlighted a functional role for pRb in controlling cellular metabolism. Here, we report that loss of the gene encoding pRb (Rb1) in a transgenic mutant Kras-driven model of lung cancer results in metabolic reprogramming. Our tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Moreover, we observed significant differences in genomic alteration patterns between the 4 metabolic subgroups. RB1 is a well-known tumor suppressor gene, and its deletion can enhance glycolytic metabolism and driving tumor progression [ 43 ]. A recent study also identified LRP1B, which encodes low-density lipoprotein receptor-related protein 1B, as a novel tumor suppressor, and LRP1B deletion was associated with chemotherapy resistance in ovarian cancer [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we observed significant differences in genomic alteration patterns between the 4 metabolic subgroups. RB1 is a well-known tumor suppressor gene, and its deletion can enhance glycolytic metabolism and driving tumor progression [ 43 ]. A recent study also identified LRP1B, which encodes low-density lipoprotein receptor-related protein 1B, as a novel tumor suppressor, and LRP1B deletion was associated with chemotherapy resistance in ovarian cancer [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“… 21 In the kras‐driven lung cancers, loss of RB1 promotes a glycolytic phenotype but does not alter pyruvate oxidative metabolism or glutamine inactivation. 22 It has been suggested that EGFR/TP53/RB1 mutant lung cancers have a unique risk of histological transformation, with 25% of lung cancers exhibiting ab initio small cell lung cancer or eventual small cell transformation. 23 Another meta‐analysis has shown that loss of RB1 function leads to a 1.6 two‐fold increase in the mortality of patients with osteosarcoma, a significant increase in osteosarcoma metastasis, and a notable decrease in osteosarcoma response to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the regulation of CDK4 on cancer metabolism is predominantly exerted by its direct effect or via insulin secretion will require further elucidation. Meanwhile, the loss of Rb can also lead to a dependence on the metabolism of aerobic glycolysis 57‐60 …”
Section: Glucose Metabolism and Cell Cyclementioning
confidence: 99%
“…Meanwhile, the loss of Rb can also lead to a dependence on the metabolism of aerobic glycolysis. [57][58][59][60]…”
Section: Glucose Homeostasismentioning
confidence: 99%